Community Compliance with Health Regulations during the COVID-19 Pandemic - Yulianita, Henny; Priladani , Dhea Shobriana; Setyorini, Dyah; Sugiharto, Firman; Somantri, Irman; Eriyani, Theresia; Komariah, Maria (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aim: This study aimed to describe of community compliance in implementing health regulations during the COVID-19 pandemic in the Panyileukan subdistrict, Bandung, West Java, Indonesia. Method: The study was quantitative descriptive research.  The study population was residents who live Panyileukan District (N=242). The sampling technique used was purposive sampling (n=77). Data were collected using the modified self-report questionnaire regarding adherence in implementing health protocol which were valid and reliable. Data were analyzed using descriptive statistics and presented in frequency distribution tables and diagrams. Results: The results show that more than half of the respondents (56%) complied with the health regulations. The indicators show that 55.8% wore masks, 53.2% washed hands, 62.3% maintained social distance, and 54.5% increased their immune systems. Regarding the response dimensions, 63.6 % of respondents believed in the regulations, 55.8% accepted the regulation, and 51.9% applied the regulations. Conclusions: Most people in the Panyileukan subdistrict adhered to the health protocols. Local governments and health workers could continue facilitating, motivating, and monitoring compliance.